2012
DOI: 10.1039/c2dt12189a
|View full text |Cite
|
Sign up to set email alerts
|

Calcium manganese(iv) oxides: biomimetic and efficient catalysts for water oxidation

Abstract: CaMnO(3) and Ca(2)Mn(3)O(8) were synthesized and characterized by SEM, XRD, FTIR and BET. Both oxides showed oxygen evolution activity in the presence of oxone, cerium(IV) ammonium nitrate and H(2)O(2). Oxygen evolution from water during irradiation with visible light (λ > 400 nm) was also observed upon adding these manganese oxides to an aqueous solution containing tris(2,2'-bipyridyl) ruthenium(II), as photosensitizer, and chloro pentaammine cobalt(III) chloride, as electron acceptor, in an acetate buffer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…6-10 Artificial water oxidation catalysts have been prepared from Ca-doped manganese oxide materials to mimic the composition of the OEC, despite the limited structural understanding. 8,11-14 Other mixed metal oxides have intriguing catalytic properties, both for water oxidation and oxygen reduction. 15-19 Metal oxides are also important as battery materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6-10 Artificial water oxidation catalysts have been prepared from Ca-doped manganese oxide materials to mimic the composition of the OEC, despite the limited structural understanding. 8,11-14 Other mixed metal oxides have intriguing catalytic properties, both for water oxidation and oxygen reduction. 15-19 Metal oxides are also important as battery materials.…”
Section: Introductionmentioning
confidence: 99%
“…Although undoped manganese oxides have been demonstrated to catalyze water oxidation at low efficiencies, addition of calcium greatly increases the reaction efficiency, raising the possibility that the mechanism of dioxygen formation is related to that of the biological OEC. 11,14 XAS studies of these materials determined that the Mn centers are of the +3 and +4 oxidation state, and that the redox-inactive ions may be bridged to the Mn centers by oxido moieties in similar MMn 3 O 4 cuboidal subsites as in the OEC. 8-9 These results suggest that further understanding of PSII may allow for the rational design of more efficient heterogeneous water oxidation catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Group 2 metal ions also enhanced the rates of dioxygen activation by monometallic Mn II and Fe II complexes (16,17). Alkali and alkali earth metals have also been proposed as components in heterogeneous water oxidation by cobalt and manganese oxides (18)(19)(20)(21)(22) ) and demonstrated that the reduction potentials of the clusters are linearly correlated with the Lewis acidity of the redox-inactive metal (23).…”
mentioning
confidence: 99%
“…As many minerals possess high crystallinity and low surface area, low water oxidation activities are observed. Mixed-valence MneCa, CaMn 4 O 8 and CaMn 3 O 6 showed promising water-oxidizing activity compared to Mn oxides without Ca ions [53,56]. A soluble form of colloidal Mn(IV) oxide was also tested [55].…”
Section: Other Mn Oxidesmentioning
confidence: 99%